Development planning strategy based on local industrial potential in Surakarta City - Riskilia Amanda Putri; Sausan Salma Sagita; Effrel Maulidina Warjono; Duwi Yunitasari (Priviet Social Sciences Journal, 2026)
This study seeks to identify the leading sectors within Surakarta City and examine economic growth patterns through the lens of Klassen Typology, with the ultimate objective of formulating and evaluating appropriate strategies for enhancing the competitiveness of the batik industry. Employing a quantitative descriptive-analytical approach, this study draws upon secondary data obtained from the Central Statistics Agency or Badan Pusat Statistik (BPS) of Surakarta City and the Solo Data portal, covering the period from 2021 to 2025. The analytical framework integrates two principal methodologies, namely Klassen Typology and Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis, to provide both structural and strategic assessments of the industrial landscape. The findings reveal that the batik subsector stands as the sole base sector, with Klassen Typology positioning both the batik and birdcage industries within Quadrant I, designating them as advanced and rapidly growing subsectors, respectively. The SWOT analysis further delineates strategic directions encompassing export market expansion, technological modernization, the adoption of digital marketing platforms and the reinforcement of inter-sectoral collaboration. Collectively, these findings underscore the imperative for industrial development policies in Surakarta to be calibrated according to the distinctive characteristics of each subsector, thereby fostering subsector-specific growth trajectories that are conducive to sustainable local economic development.